CsWAK12, a novel cell wall-associated receptor kinase gene from Camellia sinensis, promotes growth but reduces cold tolerance in Arabidopsis - Wu, Qiong; Jiao, Xiaoyu; Liu, Dandan; Sun, Minghui; Tong, Wei; Ruan, Xu; Wang, Leigang; Ding, Yong; Zhang, Zhengzhu; Wang, Wenjie; Xia, Enhua (Frontiers in Plant Science, 2024)
Cold significantly impacts the growth and development of tea plants, consequently affecting their economic value. Receptor-like kinases (RLKs) are believed to play a pivotal role in signaling the plant’s response to cold and regulating cold tolerance. Among the RLK subfamilies, wall-associated receptor-like kinases (WAKs) have been investigated across various plant species and have been shown to regulate cell growth and stress responses. However, the function of WAK genes in response to cold stress in tea has not yet been studied. In a previous investigation, we identified the WAK gene family in the tea plant and isolated one specific WAK gene, CsWAK12, which is induced by abiotic stresses. Tissue expression analysis revealed that CsWAK12 had the highest expression levels in leaves compared with other tissues under normal conditions, and its transcription was rapidly induced by cold stress. Furthermore, the fusion protein CsWAK12-GFP was localized to the cell membrane. Additionally, heterologous overexpression of CsWAK12 (35S:CsWAK12) in Arabidopsis promoted plant growth by enhancing root length and seed size in natural state, although it reduced cold resistance compared to the wild type. Moreover, the cold-induced expression of C-repeat/dehydration-responsive element binding factor (CBF) genes and several key regulator genes involved in the cold stress response was diminished in Arabidopsis lines overexpressing CsWAK12. These data suggest that CsWAK12 may play a crucial role in the growth of tea plants and their response to cold stress.